(3efJNH GdJPcQI aj GdJGQjNs - (3Jbi GdOjf CHi GdYHGS CMeO Hf Ydj Hf YHO GdbGOQ GdebQjRis; (3eMeO Hf GdMSf Hf eMeO Hf Ydj Hf MeOhf, CHh GdeYGdj, HgGA GdOjf GdHZOGOj,J (B562 (3g` s
(3ChdgG (B:s
(3hHYO agPG cJGH YOje GdeKGd ai Led GdJGQjN , GfJNHJg ef cJGHi GdeSei HGdJPcQI s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg s
(3GdehLhO efg eLdO jHOC ef SjQI BOe CHj GdHTQs
(3GfXQ Qbe (B523 (3JGQjNs
(3fSNI KGfjIs
(3gfGc Tc Gf GdJPcQI ddebQjRi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B217s
Keywords: (3GdJGQjNs